EFISIENSI RELATIF KANTOR PELAYANAN PAJAK BUMI DAN BANGUNAN (KP PBB) DI JAWA TIMUR (Studi di sepuluh KP PBB) - Munawar Ismail; Suharno Suharno; Putu Mahardika A. Saputra; Fery Prasetya (Faculty of Economics and Business, Universitas Gadjah Mada, 2006)
Efficiency is an ideal condition that all kinds of institution strive to achieve. Based on this argument, the study is therefore aimed at, first, evaluating the relative efficiency of Property-Tax Offices in East Java and, second, searching factors behind of the efficiency. The study found that there were only two Property-Tax Offices (i.e: Surabaya 1 and 3) that are qualified as efficient institution over periode of study (2002-2004). While Mojokerto Property-Tax Office was efficient only in 2004. Other finding was that operational cost, consisting of water, electricity and phone costs, was the most important source of inefficiency in all samples of Property-Tax Office in East Java.